Research on the Construction of Open Management System for Teaching Laboratories in Local Universities and Colleges Under the Background of New Medical Sciences - Luo, Chenliang; Zong, Ziao; Meng, Hui; Luo, Tong; Chen, Zeqin (Journal of Research in Vocational Education, 2025)
In the era of the “New Medical Sciences” initiative, the cultivation of medical talents aims to foster high-quality medical students with profound theoretical knowledge, excellent practical skills, and a commitment to clinical services, further enhancing their clinical reasoning ability and practical innovation capacity. Cultivating college students with innovative capabilities is one of the core objectives for multi-level and high-standard talent development in medical universities under the New Medical Sciences framework. This paper systematically analyzes the main challenges encountered in exploring the cultivation of college students’ innovative abilities through the opening of teaching laboratories in local universities. It proposes a four-level closed-loop governance mechanism of “University-Management-Teacher-Student” and synergistically advances structural reforms on both the supply and demand sides. By improving the governance capacity and operational efficiency of laboratory opening from multiple dimensions, this study strengthens the cultivation of students’ practical abilities and innovative literacy, thereby providing a theoretical basis and practical path for nurturing compound medical innovative talents under the background of New Medical Sciences.